OPTIMIZATION OF LEVOTHYROXINE THERAPY BASED UPON COMPLEX EVALUATION OF HORMONAL AND IMMUNE STATUS IN THE PATIENTS WITH SUB-CLINICAL AND MANIFESTING HYPOTHYREOSIS - I. V. Sarvilina; E. F. Shin; Yu. V. Gorshkova (Медицинская иммунология, 2014)
Abstract.The aim of present study was complex evaluation and analysis of hormone and immune profiles in the patients with subclinical and manifesting thyroid hypofunction, taking into account a therapeutic drug monitoring for optimization of levothyroxine treatment. Forty patients with thyroid hypofunction are included into the study: I group, patients with subclinical hypothyreosis (n=19) and the levels of thyroxine-binding globuline exceeding 700 nmol/l, who received levothyroxine at 50 μg daily after withdrawal of drugs for 10 days; II group, the patients with manifesting hypothyreosis (n=21), who received levothyroxine at 100 μg daily. A significant regress of clinical signs of hypothyreosis was registered in both groups following 3 months of receiving levothyroxine, employing an optimized mode of dosage. An immune/endocrine component is shown for the mechanism of levothyroxine action, which promotes the development of maximal hormonal effect, with respect to improvement of life quality in the patients with hypothyreosis upon optimization of therapy based on the therapeutic drug monitoring using liquid chromatography/mass-spectrometry.